2013
DOI: 10.1371/journal.pone.0052239
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Rare Recurrent Copy Number Variants in High-Risk Autism Families and Their Prevalence in a Large ASD Population

Abstract: Structural variation is thought to play a major etiological role in the development of autism spectrum disorders (ASDs), and numerous studies documenting the relevance of copy number variants (CNVs) in ASD have been published since 2006. To determine if large ASD families harbor high-impact CNVs that may have broader impact in the general ASD population, we used the Affymetrix genome-wide human SNP array 6.0 to identify 153 putative autism-specific CNVs present in 55 individuals with ASD from 9 multiplex ASD p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 70 publications
4
64
0
1
Order By: Relevance
“…With specificity levels as high as 98%, the GeoPref test was able to signify ASD status in a subset of individual toddlers with very high accuracy and as such may be more powerful than other biomarker attempts including those at the behavioral (2931), genetic (3234), and neuroimaging levels (3537). Eye-tracking technology is attractive as a potential tool in early identification and clinical evaluation efforts because patterns of eye gaze are objective, quantifiable behaviors based on neural systems known to be abnormal in ASD, such as the visual attention system (3840).…”
Section: Discussionmentioning
confidence: 99%
“…With specificity levels as high as 98%, the GeoPref test was able to signify ASD status in a subset of individual toddlers with very high accuracy and as such may be more powerful than other biomarker attempts including those at the behavioral (2931), genetic (3234), and neuroimaging levels (3537). Eye-tracking technology is attractive as a potential tool in early identification and clinical evaluation efforts because patterns of eye gaze are objective, quantifiable behaviors based on neural systems known to be abnormal in ASD, such as the visual attention system (3840).…”
Section: Discussionmentioning
confidence: 99%
“…Additional probe enrichment targeted genomic regions identified by our prior studies and identified elsewhere in the medical literature. These regions included published copy number variants and individual genes associated with DD/ID/ASD [2029]. The increase in analytical sensitivity resulting from this additional 3.3% probe content has been calculated to be 2.6% [19].…”
Section: Methodsmentioning
confidence: 99%
“…The custom iSelect array was processed on 3,000 case and 6,000 control samples at the Center for Applied Genomics at The Children’s Hospital of Philadelphia (CHOP) [27]. The same array was also used to analyze DNA from 196 Utah discovery cohort family members at the University of Utah Genomics Core facility for variant validation and analysis of SNP segregation in families.…”
Section: Methodsmentioning
confidence: 99%